Accurate Training For Accounting Students At Smk Islamiyyah Sapugarut - Ainin Nimah; Tri Khoiril Ikhlakh; Zakiyah Mubarok (Amala Jurnal Pengabdian Kepada Masyarakat, 2025)
Accurate is an Indonesian accounting software designed to make financial reporting easier, faster, and more precise, which has attracted widespread use among entrepreneurs. To prepare vocational students with relevant competencies, SMK Islamiyyah Sapugarut Pekalongan-an institution with an accounting program-requires training that integrates computerized accounting. This community service program was carried out through training sessions on the use of Accurate for Class XI Accounting students. The methods included lectures to explain the basic concepts of computerized accounting, tutorials to guide students in operating Accurate, and discussions to address practical problems. The results showed that students were able to understand the basic features of Accurate and practice preparing simple financial reports. The program was well received by both students and teachers, as it provided valuable hands-on experience and complemented manual accounting practices. This activity demonstrates the importance of equipping vocational students with digital accounting skills to improve their readiness for the workforce.